2015
DOI: 10.1007/s10903-015-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy as a Mediator of the Relationship Between the Perceived Food Environment and Healthy Eating in a Low Income Population in Los Angeles County

Abstract: Background-While previous studies have described psychosocial and environmental factors that contribute to healthy eating, much remains unknown about the interactions between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
(28 reference statements)
3
14
0
Order By: Relevance
“…Exceptions were two repeated cross-sectional studies by Colchero et al [31] and Jilcott Pitts et al [32] and two longitudinal studies by Meyer et al [33] and Rummo et al [34]. Thirty studies were conducted in an adult population [25,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59], seven were focused on adolescents [60,61,62,63,64,65,66] and six were conducted in a mixed age population [31,67,68,69,70,71]. Consumption or purchase of F & V were used as measure of dietary behavior in twenty-eight studies [32,34,35,36,37,38,39,40,42,43,44,46,48,49,52,53,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exceptions were two repeated cross-sectional studies by Colchero et al [31] and Jilcott Pitts et al [32] and two longitudinal studies by Meyer et al [33] and Rummo et al [34]. Thirty studies were conducted in an adult population [25,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59], seven were focused on adolescents [60,61,62,63,64,65,66] and six were conducted in a mixed age population [31,67,68,69,70,71]. Consumption or purchase of F & V were used as measure of dietary behavior in twenty-eight studies [32,34,35,36,37,38,39,40,42,43,44,46,48,49,52,53,…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen out of the twenty studies were conducted in the USA. Most of these twenty studies considered more than one aspect of the food environment: fourteen papers considered availability and quality of stores in the neighborhood [32,35,38,39,40,41,42,43,53,56,57,59,67,68]; ten papers studied access, distance or time taken to travel to stores [32,36,37,40,43,57,58,59,60,67,68]; and seven papers studied economic aspects of the food environment such as objective food cost and/or perceived affordability [32,43,53,54,55,56,67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also shown that having social support (or positive social influences and encouragement from others to engage in healthy eating) was associated with higher diet quality [31,32,33,34]. Similarly, self-efficacy has been shown to predict diet quality in different target populations [35,36,37,38]. Barriers to healthy eating such as cost and finances, availability and convenience, absence of fruits and vegetables in the home, and lack of knowledge regarding healthy foods have also been associated with the diet quality of African Americans [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our study suggest that dietary behaviors of socioeconomically disadvantaged adults may be improved by modifying the physical and social environments. For example, healthy dietary behaviors could be adopted or maintained by enhancing perceptions of access to healthy food, identifying where to buy healthy foods, where affordable healthy food might be offered in the community, and how to get to these locations (Gase et al, 2016). In addition, sharing healthy cooking tips with neighbors through community programs or health fair events promoting a healthy community may also improve an individual's perception of the social environment and, in turn, dietary behaviors.…”
Section: Discussionmentioning
confidence: 99%